Effect of land restitution programme on households' food security in Limpopo Province of South Africa : a case study of Waterberg District - Mantsho, Stephen Mozindo (My University, 2018)
The Land Restitution Programme was designed to assist farmers through support for infrastructure, marketing, finance and extension services. This initiative was intended to support job creation, food security and support agricultural growth. Nevertheless, poverty and food insecurity have profound implications for health and welfare. However, household dietary diversity score has long been recognized by nutritionists as a key element of high-quality diets. This study examined the effects of the land restitution on households’ food security in Waterberg district. The objectives of this study were to profile households’ socioeconomic/ demographic characteristics, assess the food security status of land restitution beneficiaries and non-beneficiaries, examine the effects of Land Restitution Programme on food security and investigate the challenges faced by smallholder farmers in accessing land and other inputs for agricultural purposes in Waterberg district. Primary data was collected from 110 smallholder farmers using purposive and random sampling techniques. Dietary diversity score was used to assess the food security status of land restitution beneficiaries and non-beneficiaries while logistic regression model was used to examine the effect of Land Restitution Programme on their food security status. The results of dietary diversity score revealed that 70% of the households were food secure while 30% of the households are food insecure. The age of the household head, access to the market and land size were found to be positively significant at 10% level while beneficiary status was found to be positively related to food security status and significant at 5% level. Variables which were found positively significant at 1% level are gender of the household head, off-farm income and access to credit. Problems affecting households differs from lack of access to credit facilities to lack of grazing land. Based on the findings the study recommends prioritisation of women agricultural projects; diversification of income; provision of smallholder credit facilities in rural areas and provision land to farmers so that they increase their production which give them an advantage to become food secure. Key words: Dietary diversity, logit model, food security and Land restitution.
Thesis (M.Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2018
Keywords: Dietary diversity; Logit model; Food security; Land restitution; Land reform -- South Africa -- Limpopo; Land settlement -- South Africa -- Limpopo; Food security